2019
DOI: 10.1021/acsami.9b14631
|View full text |Cite
|
Sign up to set email alerts
|

Air Plasma-Enhanced Covalent Functionalization of Poly(methyl methacrylate): High-Throughput Protein Immobilization for Miniaturized Bioassays

Abstract: Miniaturized systems, such as integrated microarray and microfluidic devices, are constantly being developed to satisfy the growing demand for sensitive and highthroughput biochemical screening platforms. Owing to its recyclability, and robust mechanical and optical properties, poly(methyl methacrylate) (PMMA) has become the most sought after material for the large-scale fabrication of these platforms. However, the chemical inertness of PMMA entails the use of complex chemical surface treatments for covalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…This evidence demonstrates that air-plasma treatment can significantly improve the biocompatibility of inorganic implants and may be conducive for osteogenesis. After air-plasma treatment, hydroxyl radicals are added to the treated surface (Tsougeni et al, 2015;Kurzyp et al, 2017;Sathish et al, 2019;Wieland et al, 2020;Zhang et al, 2020), further reducing water contact angle shown in Figure 4, which forms an adsorption effect with adhesion proteins and enhances biocompatibility. Hydrophilicity is critical for the bioactivity of bone tissue implants and can improve cell adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence demonstrates that air-plasma treatment can significantly improve the biocompatibility of inorganic implants and may be conducive for osteogenesis. After air-plasma treatment, hydroxyl radicals are added to the treated surface (Tsougeni et al, 2015;Kurzyp et al, 2017;Sathish et al, 2019;Wieland et al, 2020;Zhang et al, 2020), further reducing water contact angle shown in Figure 4, which forms an adsorption effect with adhesion proteins and enhances biocompatibility. Hydrophilicity is critical for the bioactivity of bone tissue implants and can improve cell adhesion and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody embedded lubricant‐infused surfaces were created on PMMA, a low‐priced polymer with many advantages such as optical transparency, durable chemical and mechanical properties, and recyclability. [ 57,58 ] PMMA surfaces were first oxygen plasma treated to induce hydroxyl groups on the surface, and then fluorosilanized via chemical vapor deposition (CVD) of trichloro(1 H ,1 H ,2 H ,2 H ‐perfluorooctyl)silane followed by heat treatment at 90 °C to promote the hydrolysis and condensation reactions. Immediately after the plasma treatment, the hydrophilicity of the surface can cause adsorption of water molecules on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The microfluidic chlamydia assay module was fabricated by first covalently immobilizing MOMP (50 µg/mL) onto PMMA substrates, using our developed air-plasma enhanced bio-functionalization strategy. 6 Next, double-sided adhesive tapes were cut to form microchannels using a carbon dioxide laser cutter (VLS 3.50, Universal Laser Systems, USA), and bonded to the MOMP-functionalized PMMA strips on one side and IPA-cleaned PMMA strips on the other side to complete the microfluidic device ( Figure 1B). The bare surfaces of the PMMA microchannels were finally blocked with 1% weight/volume of bovine serum albumin, to prevent nonspecific adsorption of proteins, and attached to the upper portion of the FHD using M3 bolts to complete the assembled prototype.…”
Section: Methodsmentioning
confidence: 99%
“…The microfluidic chlamydia assay module was fabricated by first covalently immobilizing MOMP (50 µg/mL) onto PMMA substrates, using our developed air‐plasma enhanced bio‐functionalization strategy 6 . Next, double‐sided adhesive tapes were cut to form microchannels using a carbon dioxide laser cutter (VLS 3.50, Universal Laser Systems, USA), and bonded to the MOMP‐functionalized PMMA strips on one side and IPA‐cleaned PMMA strips on the other side to complete the microfluidic device (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%